LEMAHNYA PENEGAKAN HUKUM DI INDONESIA DARI SUDUT PANDANG STRUKTURAL - Adriani Adnani (Ensiklopedia of Journal, 2022)
As a body politic was really of course that law constitutesa slate base. Its fact is oftentimes jurisdictional is ruled out, there are many deviation happening of what does be expecte. Most more if concerns by aught structural facet. Of this structural viewpoint really appears really how its frail law at Indonesian